Literature and Politics : Pushing the World in Certain Directions. - Marks, Peter (Cambridge Scholars Pub., 2012)
George Orwell argued that one of the four great motives for a prose writer was the desire 'to push the world in a certain direction, to alter other people's idea of the kind of society that they should strive after'. This book contains exciting new work by established and emerging scholars that explores political literature over the last century and a half. It shows how, from The Communist Manifesto to the dystopian future of Margaret Atwood's Oryx and Crake, writers have attempted to alter p ...